Global trends in research of endoscopic thyroidectomy from 2013 to 2022: a scientometric and visualization analysis - Zheng, Daitian; Yang, Qiuping; Wu, Jinyao; Zhou, Zhongming; Cai, Jiehui; Chen, Lingzhi; Ji, Zeqi; Tian, Huiting; Li, Zhiyang; Chen, Yexi (Frontiers in Endocrinology, 2023)
Introduction Recently, endoscopic thyroidectomy has been developed and applied to thyroid surgery to achieve minimized neck scar formation and enhanced aesthetic outcomes. Our scientometric research in this paper offers a thorough overview of endoscopic thyroidectomy from 2013 to 2022. Methods All pertinent articles on endoscopic thyroidectomy were obtained from the Web of Science Core Collection Database. The data on the number of citations and publications, most prolific countries and institutions, significant authors and journals, top themes, and keywords were analyzed by Biblioshiny, CiteSpace, and VOSviewer. Results There were 758 publications, all of that were found from 2013 to 2022. The output of the annual publication showed an upward trend. A series of cases report by Anuwong et al. published in 2016 received the most citations. The country with the most articles published articles was South Korea, and the two countries with the most collaboration were South Korea and the United States. The most productive journal was Surgical Endoscopy and Other Interventional Techniques. Dionigi G, Kim HY, and Anuwong A were the writers with the most articles published, the highest h- and g-indices, and the strongest link strength, respectively. The keywords “endoscopic thyroidectomy”, “surgical”, “thyroidectomy”, “robotic thyroidectomy”, “experience”, and others were most used. Conclusion The innovative surgical technique, transoral endoscopic thyroidectomy vestibular approach (TOETVA), leaves no scars and produces optimal cosmetic results. However, the long-term oncologic results for thyroid cancer performed with this approach are still missing. This scientometric analysis can offer valuable insights into the present research standing and key focal points in this domain, enabling researchers to gain a precise understanding of the state-of-the-art research in this area.